Student Perceptions of Online Learning in Physiotherapy - Arsovski, Denis; Chichevska Jovanova, Natasha (Medical Rehabilitation, 2025)
Introduction: The COVID-19 pandemic increased the scope for online lessons in physiotherapy, a profession with hands-on practice and direct interaction. While digital platforms provide accessibility and flexibility, they also introduce some challenges, affecting the quality of education. Objectives: Objectives: The aim of this study is to investigate the perceptions of physiotherapy students for online learning, with focus on its advantages, challenges and preferred future directions in the education of physiotherapy students. Methods: Methods: In the present study, 122 physiotherapy students from educational institutions in North Macedonia and Bulgaria were included in this research. Data were collected via an online questionnaire that allows to assess demographics, the perceived benefits, challenges and preferences regarding blended learning. Quantitative data were analysed with descriptive statistics, chi-square tests and analysis of variance with post-hoc comparisons. Qualitative responses showed further information about the experience of the students with online learning. Results: Results: Students showed a preference for blended learning models with combination of online and in-person education. On line learning was valued for its flexibility and accessibility, but the challenges such as limited personal training, technical difficulties and reduced teacher-student interaction were noted. Satisfaction levels varied across academic years (p<0.001) with younger students reporting higher satisfaction than advanced students, who required more practical training. Key barriers were insufficient digital tools and digital literacy. Conclusion: Conclusion: While online learning improves accessibility, it must be integrated with in-person training for competency in clinical skills. Future research should be focused on digital literacy, technical support and interactive content for optimising blend ed education in physiotherapy
Keywords: physiotherapy education, physical therapy modalities, rehabilitation, blended learning, clinical competence